Intimate partner violence among HIV-positive women in discordant relationships attending care and treatment clinics in Dar es Salaam, Tanzania - Mathania, Milka; Sirili, Nathanael (Frontiers in Public Health, 2023)
Background Intimate partner violence (IPV) toward women is a public health concern affecting many countries across the world. Globally, 30% of women experience lifetime physical, sexual, or psychological harm. HIV-positive women in discordant relationships are at higher risk of experiencing IPV more than other women. This study aimed to determine magnitude and factors associated with intimate partner violence among HIV positive women in discordant relationships attending HIV care and treatment clinics in Dar es salaam, Tanzania Methods An analytical cross-sectional study was conducted among 411 HIV-positive women who were in discordant relationships attending HIV care and treatment clinics in eight selected health care facilities in Dar es salaam from 21st June 2021 to 11th July 2021. A questionnaire with structured questions pertaining to social and demographic information and factors associated with intimate partner violence was used. Data were collected electronically using the Open Data Kit (ODK) system, cleaned, and stored. Descriptive analysis was done and presented in frequency distribution and cross-tabulation. Chi-square was used to determine the differences in variables and the Modified Poissons regression model was used to estimate adjusted prevalence risk ratios with 95% CI for factors associated with IPV. variables were considered statistically significant at 95% CI and p< 0.05. All statistical analyses were conducted using STATA version 15. Results The mean age of the participants was 36.2 (SD 7.8). The majority of women had attained primary education, 237(57.7%). Over sixty percent (65.7%) of HIV positive women in discordant relationships had ever experienced IPV. Women whose partners had primary and secondary education level, alcohol users, and solely decision-makers in the family were strongly associated with IPV. Conclusion Close to two-third of HIV-positive women who were in discordant relationships attending HIV care and treatment clinics in selected health care facilities in Dar es salaam experience IPV. Low level of education of the partner, alcohol use and power relation in decision making were the factors that were significantly associated with IPV. We recommend for routine screening of IPV for HIV-positive women who in discordant relationships attending HIV clinics. Joint efforts are needed in addressing the factors associated with IPV.